Constitution and the Limitation of Power: Montesquieu's Perspective - Yunus, Nur Rohim (ADALAH, 2023)
This essay discusses the importance of limiting power in a government system to prevent abuse of authority and maintain a balance of power between state institutions. Through his theory of separation of powers in The Spirit of Laws (1748), Montesquieu emphasized that power should be divided into three main branches—legislative, executive, and judicial—to provide checks and balances. From a philosophical, sociological, and legal perspective, this essay examines how the constitution is a primary instrument in regulating power distribution. It also discusses the debate about the extent to which limitations on power should be applied so as not to hinder the effectiveness of government. Ultimately, this essay asserts that a well-designed constitution limits power and ensures the rule of law, democracy, and justice for all people.